On the thickness and layup dependence on failure mechanisms during unfolding of curved woven composites - R.D.R. Sitohang; S. Benou; L.L. Warnet; R. Akkerman (Composites Part C: Open Access)
This study investigates the failure mechanisms of curved woven Glass/Polyphenylene sulfide (G/PPS) composites and characterizes the critical strains associated with the occurrence of damages during unfolding. Tensile-bending tests were carried out to study the damage development. The damages were observed by using acoustic emission sensors, a scanning electron microscope, and a camera. The results for the (0,90) ply orientation showed that the mechanism of failure changes from intraply-dominated to interply-dominated as the laminate thickness increases. Furthermore, the change in layup for the thinnest samples, with [(0,90)]2s, [(90,0)]2s, and [(±45)]2s layups, caused a change in the mode of the damage initiation, although all of them showed initiation at the fiber/matrix interfaces. Intra-yarn cracks were found at the compression side of all 4-ply samples. These cracks caused surface yarn buckling in the [(0,90)]2s and [(±45)]2s samples, but not in the [(90,0)]2s.